Men in Ministry: Comparing Deacons and Candidates on Religiosity, Leadership, Personality, and Worship–Work Behaviors. Issue 3 (2nd July 2016) - Ferrari, Joseph R.
ABSTRACT: In the present study, 424 men in formation ("candidates") and a random sample of 424 ordained deacons reported their religious and spiritual attitudes, leadership styles, personality dimensions, and worship- and work-related behaviors. There were no significant differences between candidates and deacons on religiosity, personality, and most leadership styles. Candidates reported significantly higher worship-related behaviors than deacons, who expressed significantly higher personal-life desires. Candidates over time did not report significantly greater religiosity, personality, or leadership skills during their formation years. Results suggest that Catholic deacons and men in diaconate formation are similar as they start and continue their life as permanent ministers.